2009
DOI: 10.1179/174328109x445660
|View full text |Cite
|
Sign up to set email alerts
|

Metallic iron whisker formation and growth during iron oxide reduction: K2O effect

Abstract: An attempt has been made to clarify metallic iron whisker growth and swelling behaviour during iron oxide reduction in the presence of K 2 O alkali. Annealed pure and K 2 O doped wü stite compacts were isothermally reduced in a thermogravimetric apparatus with CO gas at 800-1100uC. The reduction rate increased with temperature but decreased with increasing K 2 O content. Morphologically, by increasing reduction temperature, porosity and whisker growth of the metallic iron produced increased, which in turn lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 15 publications
1
22
0
Order By: Relevance
“…catastrophic swelling, which may exceed 400% in volume at worst. [4][5][6] This catastrophic swelling is a characteristic of pellets and has been not observed either in sinter or in lump ores.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…catastrophic swelling, which may exceed 400% in volume at worst. [4][5][6] This catastrophic swelling is a characteristic of pellets and has been not observed either in sinter or in lump ores.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling can be categorized into normal swelling, up to 20% in volume, [1][2][3][4][5] and abnormal, i.e. catastrophic swelling, which may exceed 400% in volume at worst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction swelling results attained in this study indicate that large amounts of potassium in the reducing atmosphere promote pellet swelling, nevertheless including within the range of normal swelling (up to 20% in volume 16) ). The observation is opposite to the study by Bahgat et al,16) in which swelling clearly decreased with increasing the amount of added K2O to wüstite compacts during isothermal reduction. However, it must be taken into account that potassium was added as K2O there, not being in the gaseous form.…”
Section: Fig 12mentioning
confidence: 57%
“…10,15) The effect of potassium on the reduction swelling behaviour has been investigated only in a few studies. Bahgat et al 16) found that swelling and the reduction rate of wüstite compacts both decreased with increasing K2O content. The effect of sodium on the swelling of hematite during reduction has been studied by Lu.…”
Section: Introductionmentioning
confidence: 99%